2018
DOI: 10.4314/bcse.v32i2.4
|View full text |Cite
|
Sign up to set email alerts
|

Removal of heavy metals Pb(II), Cd(II) and Cu(II) from waste waters using synthesized chromium doped nickel oxide nano particles

Abstract: ABSTRACT. Adsorption of metal ions Pb(II), Cd(II) and Cu(II) are observed on chromium doped nickel nano metal oxide. Chromium doped nickel oxide was synthesized by combustion technique using glycine as a fuel. In this work, transmission electronic microscopy (TEM), scanning electronic microscopy (SEM), X-ray diffraction (XRD) and Brunauer-Emmett-Teller (BET) are applied to study the composition and structure of chromium doped nickel oxide. Batch equilibrium experiments were performed to study the removal effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The nanoparticles appear to be spherical in shape with an average size of 10-130 nm. Recent studies have shown the application of chemical precipitation, adsorption, oxidation-reduction, evaporation, ionic exchange, electrochemical treatment, and membrane separation techniques in metal extraction from wastewaters (Krishna, 2018). Removal of toxic pollutants by adsorption on metal oxides has shown immense potential.…”
Section: Resultsmentioning
confidence: 99%
“…The nanoparticles appear to be spherical in shape with an average size of 10-130 nm. Recent studies have shown the application of chemical precipitation, adsorption, oxidation-reduction, evaporation, ionic exchange, electrochemical treatment, and membrane separation techniques in metal extraction from wastewaters (Krishna, 2018). Removal of toxic pollutants by adsorption on metal oxides has shown immense potential.…”
Section: Resultsmentioning
confidence: 99%